Red emitting Eu3+ induced SrWO4 materials: synthesis, structural, morphological and photoluminescence analysis. (16th September 2021) - Saravanakumar, S; Sivaganesh, D; Sivakumar, V; Sasikumar, S; Thirumalaisamy, T K; Sayed, M A; Ali, Atif Mossad
Abstract: Rare-earth doped phosphors have occupied significant percentage in the field of luminescence applications. In order to get the optimized intensity of PL spectra, the dopant selection, dopant concentration and preparation technique plays a major role. In this work, SrWO4 and Eu 3+ doped SrWO4 were successfully synthesized via fuel assisted solid state reaction technique at a temperature of 900 °C. The effect of Eu concentration on SrWO4 was analyzed by X-ray diffraction, scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and PL spectroscopy. All the diffraction peaks of prepared SrWO4 and Sr1−x Eux WO4 (x = 0.01, 0.02, 0.03, 0.04 and 0.05) were well-matched with the standard tetragonal phase of SrWO4 . In the PL study, SrWO4 :Eu 3+ shows the characteristics emission peaks at 5 D0  →  7 FJ (J = 1, 2, 3, 4) transitions for Eu 3+ . 5 D0  →  7 F2 (615 nm) is predominant at 394 nm excitation wavelength. The PL emission intensity at 615 nm gradually increases upto 4% of Eu 3+ and then decreases. Using XPS, the chemical state analysis was carried out in Sr1−x Eux WO4 (x = 0.04) and Eu dopant is in 3 + oxidation state. The electron density distribution analysis in the unit cell was carried using the maximum entropy method (MEM) and their charge derived properties were correlated with the PL analysis. Based on the different characterization analysis, Eu 3+ doped SrWO4 act as an efficient red-emitting phosphor for Near UV (394 nm excitation), blue LED (450 nm excitation) based white LED and FED applications.